THE IMPACTS OF SPEECH ACTS TO THE EFL TEACHER AND THE STUDENTS’ ACTIVENESS IN THE TEACHING LEARNING PROCESS - Amir, Nursakinah (Ekspose: Jurnal Penelitian Hukum dan Pendidikan, 2023)
This research aims at identifying (1) the kinds of speech act which are performed by the teacher in Indonesian EFL classroom in terms of locutionary, illocutionary and perlocutionary, (2) The function of speech act produced by the teacher, (3) The impacts of speech act to the teacher’s and students activeness in teaching and learning process. This research employed both qualitative and quantitative method. The data were in the form of utterances spoken by the EFL teacher when teaching in the classroom. The researcher planned, collected, analyzed and reported the research findings. The steps of collecting the data were taking video of the EFL teacher when he was teaching in the classroom, transcribing what the teacher said, selecting the data, classifying the data, transferring the data into table, analyzing and interpreting the data. The findings showed that the EFL teacher commonly uses illocutionary act in his teaching. He performs mostly directives as the illocutionary acts as he often asks the students to do some works or activities. Giving instruction or command helps him to run the EFL class.  Penelitian ini bertujuan untuk mengidentifikasi (1) jenis tindak tutur yang dilakukan oleh guru di kelas EFL bahasa Indonesia ditinjau dari lokusi, ilokusi, dan perlokusi, (2) Fungsi tindak tutur yang dihasilkan oleh guru, (3) Dampaknya tindak tutur terhadap keaktifan guru dan siswa dalam proses belajar mengajar. Penelitian ini menggunakan metode kualitatif dan kuantitatif. Datanya berupa ucapan yang diucapkan oleh guru EFL saat mengajar di kelas. Peneliti merencanakan, mengumpulkan, menganalisis dan melaporkan temuan penelitian. Langkah-langkah pengumpulan data adalah mengambil video guru EFL ketika dia mengajar di kelas, menyalin apa yang dikatakan guru, memilih data, mengklasifikasikan data, mentransfer data ke dalam tabel, menganalisis dan menafsirkan data. Temuan menunjukkan bahwa guru EFL umumnya menggunakan tindak ilokusi dalam pengajarannya. Ia lebih banyak melakukan arahan sebagai tindak ilokusi karena ia sering meminta siswa melakukan suatu pekerjaan atau aktivitas. Memberikan instruksi atau perintah membantunya menjalankan kelas EFL